Empowering Journal Managers as an OJS-Based Community Service Activity - Muh. Akbar Fhad Syahril; Arini Asriyani (Lembaga Penelitian dan Pengbdian Masyarakat (LP2M) Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This article aims to describe the role of the manager's journal devotion to the public as a form of real activity devotion, through routine management journals that are conducted in a way systematic and sustainable. Manager journal not only operates the administrative publishing function, but also carries out the educational and facilitative functions for authors, reviewers, and the academic community. Through the selection process script, giving back substantive and technical, implementation ethics publication, compilation guide authors, and utilisation of Open Journal Systems (OJS), the management journal contributes directly to the increase in quality articles and strengthening of governance, a transparent and accountable journal. Study results show that routine management journal impact on increasing the understanding of writers to structure article devotion, skills in writing scientific, and compliance with standard citation, while strengthening digital literacy publications through mentoring OJS usage. Activities also support achievement indicator performance, the Three Pillars College, especially in the aspect of devotion to public-based external scientific publications. Thus, the experience management journal can be positioned as a model of devotion to strategic society, because​ in a way simultaneously increases the capacity of writers, quality of publications, and the scientific publication ecosystems in the college.